2013
DOI: 10.1371/journal.pone.0057536
|View full text |Cite
|
Sign up to set email alerts
|

Deaths and Medical Visits Attributable to Environmental Pollution in the United Arab Emirates

Abstract: BackgroundThis study estimates the potential health gains achievable in the United Arab Emirates (UAE) with improved controls on environmental pollution. The UAE is an emerging economy in which population health risks have shifted rapidly from infectious diseases to chronic conditions observed in developed nations. The UAE government commissioned this work as part of an environmental health strategic planning project intended to address this shift in the nature of the country’s disease burden.Methods and Findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…According to the Egyptian Environment Affairs Agency, air pollution in Cairo is responsible for 3,400 deaths, 15,000 cases of bronchitis, and 329,000 cases of respiratory infection each year. Gibson et al (2013) found that outdoor air pollution was the leading contributor to mortality in UAE with 651 attributable deaths, which are~7.3 % of total deaths in 2008.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Egyptian Environment Affairs Agency, air pollution in Cairo is responsible for 3,400 deaths, 15,000 cases of bronchitis, and 329,000 cases of respiratory infection each year. Gibson et al (2013) found that outdoor air pollution was the leading contributor to mortality in UAE with 651 attributable deaths, which are~7.3 % of total deaths in 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the petrochemical industry, traffic and transported emissions from the outside of this country contributed to the remaining 28% of the total PM 2.5 [75]. to 31 μg/m 3 in 2009 [94]. Nevertheless, in the capital Doha, the average PM 10 levels in 2010 at some points exceeded the annual limit recommended by WHO [54] as a result of the combination of dust from desert storms and megaconstructions activities [94,95].…”
Section: Kuwaitmentioning
confidence: 99%
“…to 31 μg/m 3 in 2009 [94]. Nevertheless, in the capital Doha, the average PM 10 levels in 2010 at some points exceeded the annual limit recommended by WHO [54] as a result of the combination of dust from desert storms and megaconstructions activities [94,95]. A prospective cohort study population was conducted to assess the relationship between daily hospital admissions due to respiratory and CVD and the exposure to daily concentrations of air pollutants -carbon monoxide (CO), sulfur dioxide (SO 2 ), nitrates, ozone ( The slight increase observed in the concentrations of these air pollutants in the year 2005 was consistent with a similar increase in the daily hospital admissions due to respiratory, ischemic heart diseases and CVD.…”
Section: Kuwaitmentioning
confidence: 99%
“…Along the Arabian Gulf 83,600 km 2 is occupied by the UAE, with an estimated population of around 7.5 million (as of 2011). The UAE has a diversified modern economy and resultantly faces similar issues that other industrial nations do in relation to public health and environmental problems due to various industrial activities (Gibson et al, 2013a).…”
Section: Methylmercury Contaminationmentioning
confidence: 99%